Engineering Competence Frameworks and Topic Modelling - Topchyan, Tigran R. (Mathematical Problems of Computer Science, 2021)
Abstract Engineering education is often presented as frameworks made up of intended competences based on product lifecycle step models. Such are the Conceiving-Designing Implementing-Operating(CDIO) syllabus and the European e-Competence Framework (e-CF). In this article we analyze the correlation between the expert created competences implemented in these models and the job market requirement qualifications represented as topics extracted with probabilistic topic models.